Guidelines for the management and treatment of periodic fever syndromes familial mediterranean fever - Terreri, Maria Teresa R. A. [UNIFESP] (2016)
Objective: To establish guidelines based on scientific evidence for the management of familial Mediterranean fever. Description of the evidence collection method: The Guideline was prepared from 5 clinical questions that were structured through PICO (Patient, Intervention or indicator, Comparison and Outcome), to search in key primary scientific information databases. After defining the potential studies to support the recommendations, these were graduated considering their strength of evidence and grade of recommendation. Results: 10,341 articles were retrieved and evaluated by title and abstract